Antidiabetic effect of sciadonic acid on type 2 diabetic mice through activating the PI3K-AKT signaling pathway and altering intestinal flora - Chen, Lin; Jiang, Qihong; Lu, Hongling; Jiang, Chenkai; Hu, Wenjun; Yu, Shaofang; Xiang, Xingwei; Tan, Chin Ping; Feng, Yongcai; Zhang, Jianfang; Li, Mingqian; Shen, Guoxin (Frontiers in Nutrition, 2022)
Type 2 diabetes mellitus (T2DM) is a metabolic disease characterized by hyperglycemia. The aim of this work was to investigate the effect of sciadonic acid (SA) on disorders of glucolipid metabolism and intestinal flora imbalance and to further investigate its potential molecular mechanism of anti-diabetes. The experimental data indicated that SA could alleviate hyperlipidemia, insulin resistance, oxidative stress, the inflammatory response, repair liver function damage, and promote glycogen synthesis caused by T2DM. SA could also activate the PI3K/AKT/GLUT-2 signaling pathway, promote glucose metabolism gene expression, and maintain glucose homeostasis. Furthermore, 16S rRNA analysis revealed that SA could reduce the Firmicutes/Bacteroidota (F/B) ratio; promote norank_f__Muribaculaceae, Allobaculum, Akkermansia, and Eubacterium_siraeum_group proliferation; increase the levels of major short-chain fatty acids (SCFAs), such as acetic acid, propionic acid, and butyric acid; and maintain the homeostasis of the intestinal flora. In conclusion, these results suggested that SA could reshape the structural composition of intestinal microbes, activate the PI3K/AKT/GLUT2 pathway, improve insulin resistance, and decrease blood glucose levels.